Reflections on Starchitecture and What Comes Next… (EAAE Annual Conference Proceedings, 2023)
I was trained in the offices of Rem Koolhaas and Herzog & de Meuron between 2010-2019. I was exposed to ideas, processes, methods and attitudes. Architecture, in its expanded field, was constituted through masterplans, buildings, installations, strategies, research and the day to day grind of production. At a certain point, having devoted the best part of a decade to these two practices, I had given all I could and taken all I wanted. I left and entered academia.